Kedudukan Nikah Urfi dalam Sistem Hukum Keluarga Islam: Studi Komparatif Antara Legitimasi Hukum di Indonesia dan Mesir - Daud, Sulhi M; Latif, Mukhtar; Muhammad, Fauzi (Wajah Hukum, 2025)
Urfi marriage, which is a form of marriage without official registration, is an important theme in the study of Islamic family law in Indonesia and Egypt. This study aims to analyze the position of urfi marriage in the context of positive law and sharia, and its implications for the rights of women and children. In Indonesia, urfi marriage is not legally recognized because it does not meet the registration requirements stipulated in the Marriage Law and the Compilation of Islamic Law. In contrast, Egypt recognizes urfi marriage as valid according to religion, but still emphasizes the importance of registration for legal protection. This study uses a qualitative approach and comparative study methods, by analyzing legal documents, fiqh literature, and the views of scholars. The results show that although urfi marriage is recognized in sharia, this practice poses serious challenges in protecting individual rights. This study recommends the need for policy reform to bridge the gap between sharia law and the practical needs of society, in order to ensure justice and protection for all parties involved.